2022
DOI: 10.1096/fj.202200109rr
|View full text |Cite
|
Sign up to set email alerts
|

TRPC6 inhibits renal tubular epithelial cell pyroptosis through regulating zinc influx and alleviates renal ischemia–reperfusion injury

Abstract: Canonical transient receptor potential‐6 (TRPC6) has been reported to be involved in cell damage after ischemia/reperfusion (I/R) injury in target organs. While the effect and of TRPC6 on pyroptosis in renal I/R injury remain unclear. In our study, we first established the renal I/R mouse model and oxygen–glucose deprivation and re‐oxygenation (OGD/R) cell model, and investigated the impacts of TRPC6 on the pyroptosis‐related proteins using CCK‐8, western blot, ELISA, and immunofluorescence probes. Besides, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Further investigations supported the upregulation of TRPC6 in RIRI [65]. The literature is not concordant, as the downregulation of TRPC6 has also been observed in I/R tissue compared to sham tissue [66,67]. ROS-released during RIRI-are involved in both the regulation of TRPC6-expression and -gating activity as well as the initiation of autophagy [8,50,68].…”
Section: Trpc6 Is a Controversial Player In Tubular Cells Experiencin...mentioning
confidence: 91%
See 1 more Smart Citation
“…Further investigations supported the upregulation of TRPC6 in RIRI [65]. The literature is not concordant, as the downregulation of TRPC6 has also been observed in I/R tissue compared to sham tissue [66,67]. ROS-released during RIRI-are involved in both the regulation of TRPC6-expression and -gating activity as well as the initiation of autophagy [8,50,68].…”
Section: Trpc6 Is a Controversial Player In Tubular Cells Experiencin...mentioning
confidence: 91%
“…Zinc is a trace element which is essentially involved in multiple physiological processes of the organism [78]. TRPC6 markedly contributes to transmembrane Zn 2+ -transportation and Zn 2+ itself plays a key role in autophagy [66,[79][80][81]. The Zn 2+ content is increased in cells with ischemia and reperfusion.…”
Section: Trpc6 Is a Controversial Player In Tubular Cells Experiencin...mentioning
confidence: 99%
“…After a 2-week recovery period, the left renal artery and vein were occluded for 45 min. Inhibit the activation of the inflammasome NLRP4, epigenetic effect on FOXO3 expression [ 51 ] Activated protein C No Pyroptosis Mouse Bilateral renal pedicle clipping for 30 min,followed by 24 h of reperfusion Inhibit the activation of the inflammasome NLRP5 [ 52 ] Transient receptor potential-6 (TRPC6) No Pyroptosis Mouse, HK-2 cells Bilateral renal pedicle clipping for 30 min,followed by 24 h of reperfusion Inhibit the activation of the inflammasome NLRP6 [ 53 ] Salvianolic acid B (SalB) A water-soluble compound extracted from Salvia miltiorrhiza Pyroptosis Mouse, HK-2 cells Left renal pedicle clipping for 45 min, including contralateral nephrectomy Inhibit NLRP3 inflammatory vesicle activation and prevent burning-induced inflammation by decreasing intracellular ROS [ 54 ] Naringenin Flavonoids Pyroptosis Mouse, HK-2 cells The left renal artery was clamped 30 min after right-sided nephrectomy, followed by 24 h of reperfusion Inhibit inflammation by inducing HO-1 expression [ 56 ] Necrostatin-1(Nec-1) No Necroptosis Mouse, HT29 cells Bilateral renal pedicle clipping for 30 min Rip1 inhibitor [ 35 ] Nec-1f No Necroptosis Mouse, primary murine renal tubules Bilateral renal pedicle clipping for 30 min Inhibit RIPK1 and weakly inhabit ferroptosis [ 62 ] XJB-5-131 No (has shown beneficial effects in degenerative diseases) Ferroptosis Mouse Unilateral renal artery occluded for 30 min Ferroptosis inhibitor [ 48 ] Dexmedetomidine (Dex) α2-adrenergic receptor (α2-AR) agonist Ferroptosis …”
Section: Programmed Cell Death In Iri-akimentioning
confidence: 99%
“…In response to various PAMPs and DAMPs, NLRP3 oligomerizes with the adapter protein ASC to form a high molecular weight complex that recruits and cleaves pro-caspase-1, activating it and driving the maturation of IL-1β and IL-18, GSDMD cleavage, and pyroptosis. Studies have found that there are several ways to ultimately attenuate renal IRI by inhibiting the activation of the NLRP3 inflammasome, such as using hydrogen sulfide (H2S) [ 49 ], β-hydroxybutyrate (β-OHB) treatment [ 50 ], inhibiting mTORC1 with activated protein C (aPC) [ 51 ], and promoting zinc ion influx in renal TECs with transient receptor potential-6 (TRPC6) [ 52 ]. The cleavage of GSDMD by another caspase, caspase-11, promotes pyroptosis and IL-18 release in PTCs, playing a significant role in AKI.…”
Section: Programmed Cell Death In Iri-akimentioning
confidence: 99%
“…In mice, IRI has been shown to cause downregulation of transient receptor potential cation channel-6 (TRPC6), which reduces protective zinc ion influx in TEC, resulting in less A20 expression. This leads to increased activation of the NLRP3 inflammasome and increased IRI [ 92 ]. When comparing IRI in mechanically perfused rabbit kidneys with cold-stored rabbit kidneys, higher levels of A20 and lower levels of NFκB and TNF were found in perfused kidneys, leading to fewer inflammatory lesions and less necrosis [ 93 ].…”
Section: Reviewmentioning
confidence: 99%